Skepticism, Virtue Epistemology and Alethic-meliorist perspectivism - Jaume Rodríguez, Andrés Luis (Analysis. Journal of Philosophical Research, 2022)
Abstract: The aim of this article is to discuss some key concepts of the project of the epistemology of virtues developed by E. Sosa in his works A virtue epistemology (I and II) and Knowing full well at the same time it is linked with alethic and meliorist perspectivism. In particular, three questions are addressed: (1) The question concerning askepticism and its posible solution (2) A definition of knowledge that is susceptible to face the problems pointed out by Gettier (1963) and (3) a justification of the reliability of our faculties that faces the problem of epistemic circularity successfully. Finally, I point out the relation of the epistemology of virtues with perspectivism while opening new horizons such as the meliorist conception of knowledge. Keywords: Epistemic circularity,Definition of knowledge, Epistemology of virtues, Skepticism, Meliorism, Perspectivism.